Handling Public Emergencies Through E-Government Platform in Cirebon City - Halimatusa’Dia, Anisa; Buser, Buser; Hidayat, Moh. Taufik; Heryanto, Yanto (Jurnal Multidisiplin Indonesia, 2024)
E-Government is one of the solutions in improving public services based on better governance and to improve government performance, e-government-based information and communication technology is needed.  Call center 112 is one of the public service innovations in handling emergencies in Cirebon City. The purpose of this study is to find out how emergency management is handled through the standby 112 e-government platform in Cirebon City and to expose how e-government is applied in Cirebon City through Five indoctrinators from the Nograsek Theory, namely (1) Technology, (2) Process, (3) Human, (4) Organizational Culture, (5) Organizational Structure. The research method used is the Qualitative Descriptive Method, the data collection techniques used are interviews, literature, and documentation. Data analysis is carried out through 3 stages, namely Data Reduction (Simplification), Data Disclosure (Presented), and Verification or Drawing Conclusions. The results of this study show that the handling of Emergencies through the E-government Siaga 112 Platform in Cirebon City has been shown by the cooperation in the field of technology with PT. Jasnita although there are still obstacles in the field such as poor signals, in addition to that there needs to be re-socialization so that the public knows and understands related to the 112 alerts in the event of an emergency in Cirebon City.